Animal welfare in agricultural sciences: an approach from ethics of biopower and biolaw - González-Miranda, Jose Andrés (2024)
Ethical issues about the welfare of non-human animals emerged as a way of society to learn about animal production systems, caused by moral and social ethical concerns. The aim of this article is to reflect from the Costa Rica ethical-legal approach, on the use of the dominant rationality of human animals over non-human animals, addressing biopower and applying the bioethical principles which would ensure a culture of animal welfare. Animals are beginning to be increasingly considered as something more than "things". The study of the relationships between humans and non-human animals has spread to other areas beyond animal science such as animal experimentation and research. Bioethics assesses basic principles in the human relationship with animals, such as autonomy and decision-making, beneficence and to avoid suffering, non-maleficence and no cruelty to animals, and also promotes fair, equitable and humanitarian treatment. The biolaw approach can regulate bioethical criteria contributing with ideas in response to the problems in science and animal welfare. The ethical discussion on animal welfare has focused on physical pain, feelings and the need to promote spaces where animals can express biological behavior. Animal ethics focuses on the study of moral considerations that non-human animals may receive and their consequences. Social awareness on animal welfare continues to grow and bioethics committees increasingly address issues related to scientific experimentation involving animals, as well as farmers in their production systems, so it’s necessary to determine what the ethical criteria are for decision-making in bioethics committees.